De la forme urbaine à la structure métropolitaine : une typologie de la configuration interne des densités pour les principales métropoles européennes de l’Audit Urbain - Florent Le Néchet (Cybergeo, 2015)
We analyze eight dimensions of the spatial structure of metropolitan regions in Europe. Our research is based on recent literature on the quantification of internal configurations of densities. We compute eight spatial structure indicators to achieve a classification of the major metropolitan regions (Urban Audit’s "Larger Urban Zones" with over 500,000 inhabitants), using the density grid of the European Environment Agency (2002). This work provides useful insights into the diversity of metropolitan structures in Europe, and sheds new light on the comparison between the actual structure of metropolitan regions and theoretical compact and polycentric spatial structures. Our findings emphasize the need to better account for metropolitan spatial structure through a multidimensional approach in order to formulate sustainable planning models fitted to the local context.